The Influence of Perceived Ease of Use, Usefulness, and Trust on Consumer Purchase Interest in the TikTok Shop Yellow Cart Feature - Muhammad Luthfi; Mochamad Freski Dino Fava; Ramadhan Abiyasa Harianto Harianto; Muhammad Farhan Al Ghifari (Journal of Digital Business and Innovation Management, 2026)
The social commerce phenomenon has transformed consumer shopping behavior by integrating entertainment and online transactions. TikTok Shop, through its "yellow basket" feature, is at the center of this shoppertainment phenomenon . The context of this research becomes crucial following the enactment of Trade Regulation No. 31/2023, which highlighted data security issues and forced platform restructuring. This event places trust as a vital external factor, complementing internal technological factors. This study aims to analyze the influence of perceived ease of use, perceived usefulness, and trust on consumer purchase intention for the TikTok Shop yellow basket feature. This study uses a quantitative approach with a survey method through a questionnaire to active TikTok Shop users in Surabaya City. Data were analyzed using multiple linear regression to test the influence of the three independent variables on purchase intention. The theoretical framework of the study adopts a hybrid model that integrates the Technology Acceptance Model (TAM) with the Trust Theory. The results are expected to prove that the higher the perception of ease of use, usefulness, and trust, the greater the consumer's purchase intention. This research contributes to the study of consumer behavior in the post-regulation era of social commerce and provides practical recommendations for platforms in optimizing functionality and trust-building strategies to drive sales conversions.